FREQUENCY OF PIRIFORMIS TIGHTNESS IN SCIATIC PATIENTS (Journal of Medical & Health Sciences Review, 2025)
Background: Piriformis syndrome results from compression of sciatic nerve due to tightness of piriformis muscle.Objective: To determine the frequency of piriformis muscle tightness in sciatic patientsMethods: This cross-sectional study was conducted at Physical Medicine & Rehabilitation Centre, Model Town Lahore on sciatic patients with piriformis tightness from October 2023 to May 2024 and included 77 patients diagnosed with sciatica. Piriformis stretch test was used to identify piriformis tightness in sciatic patients.  The data was collected using a self-designed questionnaire and analyzed using IBM SPSS V-23. Chi-square Test was used to find the association between gender and piriformis stretch test. Results:   Out of 77 sciatic patients, 41 were male and 36 were female. Associated pain aggravating factors such as prolonged sitting 70 (90.9%) patients, sitting on hard surfaces 61(79.2%) and pain-relieving interventions like stretching 71 (92.2%) cases, massage on affected area 60 (77.9%) patients, use of hot packs to relieve pain 73(94.8%) cases were seen. Almost 57(74.0%) patients tested positive for Piriformis stretch test. A significant association was found between piriformis stretch test and gender (p-value = 0.015)Conclusion: The proportion of men to women with piriformis tightness showed slight male predominance. The majority affected were those patients who spent more time on prolonged sitting on hard surface; therefore, they were less knowledgeable about the value of physical activity. Early diagnosis and physiotherapy management with risk factor modification can help achieve better results in managing the condition.